Examining Masculinity in Short Stories “Buaian Rahim Patriarki” By Ni Wayan Wijayanti - Yostiani Noor Asmi Harini; Aisya Mardiani; Iis; Novianti Fitria Rahmadhona; Intan Satia Hotimah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The literary work in the form of a short story entitled "Buaian Rahim Patriarki" raises the issue of masculinity and patriarchy. In this modern era, women are very optimistic and aggressively voicing their rights and equality. This study aims to show the form of patriarchy and masculinity depicted in male characters. The research method used is a qualitative method with descriptive analysis. The research data is in the form of information about the theme, plot and channeling, character and characterization, setting, and language style in the short story. Data collection techniques are done by reading techniques and literature research. The results of the analysis in the short story "Buaian Rahim Patriarki" found masculinity in male characters, namely high male ego and male power in the family. Likewise, patriarchy was also found, namely the inequality of roles and positions between women and men. The findings show that patriarchy and masculinity are used as representations of the characters' views in the short story.